Legal Aspects The Use of Dashboard Cameras as an Effort to Develop Traffic Law - Andika Prawira Buana; Arfah Tjolleng; Aan Aswari (Manunggal Halim Jaya, 2021)
The development of the times and technology has an impact on traffic law and road transportation as infrastructure that is inseparable from everyday human life. The need for these infrastructure facilities will continue to increase along with the rapid growth of transportation vehicles. The potential for these developments certainly has a positive and negative impact on its implementation. The purpose of this study is to identify and analyze the urgency of using a dashboard camera and prove that the use of a dashboard camera is a development of traffic law. The method used in this study is an empirical legal research method. The results of this study indicate that the urgency of using a dashboard camera is a feature that must be installed on a vehicle because it has a good impact, including vehicle supervisors, recording events during the trip, as evidence and complementary documents for insurance claims and is a form of traffic law development.